Differential Role of Sex and Age in the Synaptic Transmission of Degus (Octodon degus) - Oliva, Carolina A.; Rivera, Daniela S.; Mariqueo, Trinidad A.; Bozinovic, Francisco; Inestrosa, Nibaldo C. (My University, 2022)
Octodon degus are a diurnal long-lived social animal widely used to perform longitudinal studies and complex cognitive tasks to test for physiological conditions with similitude in human behavior. They show a complex social organization feasible to be studied under different conditions and ages. Several aspects in degus physiology demonstrated that these animals are susceptible to environmental conditions, such as stress, fear, feeding quality, and isolation. However, the relevance of these factors in life of this animal depends on sex and age. Despite its significance, there are few studies with the intent to characterize neurological parameters that include these two parameters. To determine the basal neurophysiological status, we analyzed basic electrophysiological parameters generated during basal activity or synaptic plasticity in the brain slices of young and aged female and male degus. We studied the hippocampal circuit of animals kept in social ambient in captivity under controlled conditions. The study of basal synaptic activity in young animals (12-24 months old) was similar between sexes, but female degus showed more efficient synaptic transmission than male degus. We found the opposite in aged animals (60-84 months old), where male degus had a more efficient basal transmission and facilitation index than female degus. Furthermore, female and male degus develop significant but not different long-term synaptic plasticity (LTP). However, aged female degus need to recruit twice as many axons to evoke the same postsynaptic activity as male degus and four times more when compared to young female degus. These data suggest that, unlike male degus, the neural status of aged female degus change, showing less number or functional axons available at advanced ages. Our data represent the first approach to incorporate the effect of sex along with age progression in basal neural status.
Keywords: octodon degus; synaptic plasticity; basal synaptic transmission; aging; sex differences